Pengaruh Lingkungan Kerja, Kepemimpinan Islami, Dan Budaya Organisasi Islami Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagau Variabel Mediasi (Studi Pada Karyawan PT. Nada Surya Tunggal) - Anggraeni, Salma; Cahyono, Edi (Journal MISSY (Management and Business Strategy), 2024)
Employees are the most important element for the progress or decline of a company. To achieve company goals, of course you need workers who are based on the conditions required by the company. Therefore, good employee performance is very necessary for the survival of the company. This research aims to analyze the direct and indirect influence of the work environment, Islamic leadership, and Islamic organizational culture on employee performance, with job satisfaction as a mediating variable for PT employees. Nada Surya Tunggal with a sample of 73 respondents. Data from this research were obtained from questionnaires that had been circulated and then tested using SPSS V25. From the data analysis that has been carried out, it shows that: (1) The work environment has a negative and insignificant effect on employee performance (2) Islamic leadership has a positive and insignificant effect on employee performance (3) Islamic organizational culture has a positive and significant effect on employee performance (4 ) Job satisfaction has a positive and insignificant effect on employee performance (5) Work environment has a positive and significant effect on job satisfaction (6) Islamic leadership has a positive and significant effect on job satisfaction (7) Islamic organizational culture has a negative and significant effect on job satisfaction (8 ) Job satisfaction is unable to mediate the influence of the work environment on employee performance (9) Job satisfaction is unable to mediate the influence of Islamic leadership on employee performance (10) Job satisfaction is unable to mediate the influence of Islamic organizational culture on employee performance.